Outcomes of liver transplantation for hepatocelluler carcinoma from living donor versus deceased donor within University of Southern California San Francisco criteria: a report from Turkey - Batı, Imam Bakır; Tüysüz, Umut (Frontiers in Oncology, 2024)
Background: Hepatocellular cancer(HCC) is the most common primary liver cancer with increasing incidence. Liver transplantation (LT) has been accepted as main curative liver cancer treatment. The effectiveness of LDLT as opposed to Deceased Donor Liver Transplant (DDLT) for patients with HCC is still controversial. There is limited data comparing the long-term outcomes of patients undergoing LDLT or DDLT for HCCs that do not meet the Milan criteria. Methods: We aimed to compare the perioperative and survival outcomes of LDLT with DDLT in HCC patients.Patients underwent LT between January 2012 and December 2020 were retrospectively analyzed. There were 137 patients who met the UCSF criteria. Of these, 75 patients received LDLT and 62 patients DDLT.The primary end points in the present study were oncologic outcomes such as the recurrence rate, disease-free survival (DFS) and overall survival (OS) of LDLT and DDLT in patients with HCC. Results:PET-CT SUVmax value, the amount of erythrocyte solution (ES) as blood transfusion of red cells given and the tumor recurrence rate were significantly higher among the deceased patients recurrence, ES, PET-CT SUVmax value and tumor differentiation had significant effects on survival. In the multivariate reduced model, cox regression analysis showed significant effects of recurrence, ES, locoregional treatment response and PET-CT on survival.Albeit not significant, the one-year recurrence rate in the LDLT was similar to that in the DDLT , three-and five-year recurrence rates were higher in DDLT compared to LDLT Conclusion:There is less chance of cold ischemia time and better-quality grafts with minimal fatty changes, lower recurrence rates and similar survival rates can be achieved in LDLT compared to DDLT